An Analysis of Students’ Understanding Language Features in Descriptive Texts Using Fix-Up Strategy - Pas Sekali Telaumbanua; Feby Meuthia Yusuf; Lailatul Husna (Kilau Publishing, 2025)
The purpose of this study is to analyze students’ understanding of language features in descriptive texts by using Fix-Up Strategy in class X of SMK N 6 Padang. This article in identifying students’ difficulties in choosing simple present tense, adjectives, nouns, and adverbs when reading descriptive texts. This study used a quantitative descriptive design. Data were collected through an objective reading test consisting of 20 multiple-choice questions. This method was chosen to measure students’ ability to identify the correct language features in descriptive texts.The results of the study showed that most students demonstrated a good understanding of descriptive texts, with an average score 78. Based on the test results, 56% of students were categorized as excellent, 23% good, 9% fair, and 12% poor. However, some students still faced challenges in correctly identifying adjectives, the simple present tense, and adverbs, as reflected in specific questions where errors were commited. Therefore, further support is recommended to address these grammatical difficulties and enhance students’ mastery of language features in descriptive texts.